UPPER LIMB INJURIES IN ESPORTS AND VIDEOGAMING – A NARRATIVE REVIEW OF PATHOLOGY, RISK FACTORS AND PREVENTION METHODS - Wiktor Chrzanowski; Lidia Mądrzak; Julia Kwiecińska; Katarzyna Krzyżanowska; Władysław Hryniuk; Marta Korchowiec; Jacek Sitkiewicz; Alicja Toczyłowska; Łukasz Bialic; Mateusz Muras (International Journal of Innovative Technologies in Social Science, 2025)
Objective: The growth of esports and videogaming has led to increased upper limb musculoskeletal complaints. This narrative review synthesizes literature on injury types, prevalence, risk factors, and management to guide prevention and management. Methods: We searched PubMed and Google Scholar for English-language studies on esports and videogaming up to May 2025. Epidemiological surveys, case reports, and reviews were included if they addressed upper limb injuries. Data on prevalence, injury types (e.g., neuropathies, tendinopathies), potential pathology and risk factors, were extracted. Key findings: Up to 70% of competitive gamers report wrist and hand pain; wrist pain appears in 6%–36% and hand pain in 5%–30%. Among those gaming > 2 hours/day, 34.8% had musculoskeletal disorders. Common injuries include RSIs such as carpal tunnel and ulnar neuropathies, tendinopathies (e.g., “gamer’s thumb”), and occasional fractures or lacerations. Risk factors include prolonged sessions (5–10 hours/day), high actions per minute (APMs) (500–600), non-ergonomic setups and obesity. Only 2% seek medical care and untreated injuries can limit performance, force time off or end careers. Conclusions: Early detection and intervention are vital. Preventive measures include ergonomic optimization, regular breaks, ergonomic devices, and exercise. Educating players and involving sports medicine professionals can reduce injuries and improve gamer well-being.